Facile Access to 3,4-Disubstituted 2H-Chromenes via Domino [4+2] Annulation - Prasad, Sure Siva; Joshi, Dirgha Raj; Kim, Ikyon (Synthesis, 2020)
A highly efficient synthetic route to polysubstituted 2H-chromenes was developed utilizing a domino O-alkylation/intramolecular Horner–Wadsworth–Emmons (HWE) olefination of diarylmethylphosphonates, which were readily accessed via Lewis acid mediated one-pot three-component coupling of aldehydes, phenols, and triethyl phosphite.
Keywords: chemical space; 2H-chromenes; domino reaction; intramolecular reaction; Horner–Wadsworth–Emmons olefination; one-pot three-component reaction